Commercial Court Rulings on PKPU and Bankruptcy: the Ratio Decidendi in Balancing Creditor and Debtor Rights - Selamat Lumban Gaol; Istianingsih Sastrodiharjo (KRTHA BHAYANGKARA, 2025)
The bankruptcy of PT Sri Rejeki Isman Tbk (Sritex), one of Indonesia’s largest textile companies, attracted public and legal scrutiny due to its debt burden of approximately IDR 19 trillion. The ruling issued by the Commercial Court in this case reflects the ongoing challenge of balancing the legal interests of creditors and debtors—particularly in determining whether debt restructuring under a Suspension of Debt Payment Obligations (PKPU) is still feasible or whether bankruptcy constitutes the only legal recourse. This article examines the ratio decidendi applied by the Commercial Court in Sritex’s bankruptcy ruling, identifies the legal reasoning patterns used by judges, and evaluates the implications of such rulings for legal certainty and business practice in Indonesia. A normative juridical method is applied, supported by jurisprudential analysis and comparative assessment of similar bankruptcy cases, including Garuda Indonesia and Duniatex.The results show that the court’s decision in the Sritex case prioritizes legal certainty for creditors while leaving unresolved questions about restructuring opportunities for debtors and the continuity of business operations. The findings underscore the urgency of reforming PKPU mechanisms to become more flexible, thereby enabling companies with viable prospects to pursue restructuring prior to bankruptcy declarations.